2012
DOI: 10.1590/s1517-70762012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and study of the titanium oxide thin films doped with Tb3+ and Ce3+ ions

Abstract: In this study, we investigated the dependence of the thickness and refractive index of thin films on the withdrawal speed. The films were produced by dip-coating on a glass substrate. The hydrolytic (conventional) sol-gel method was used in the preparation of titanium alkoxide, which were obtained by homogenizing tetraethylorthotitanate stabilized by beta-diketone (2,4-pentanodione) in an alcohol solution. Potential applications, such as active planar waveguides, were evaluated by m-line spectroscopy, electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Where the refractive index at 632.8 nm wavelength increases from 2.01 to 2.33 with the increase of film thickness. Generally, the increase in film thickness improves film densification with the addition of layer deposition [13,21]. Thus, it can be concluded that the variation of the refractive index with the variation of film thickness is attributed to the increase in the film density for thicker films.…”
Section: Msementioning
confidence: 98%
“…Where the refractive index at 632.8 nm wavelength increases from 2.01 to 2.33 with the increase of film thickness. Generally, the increase in film thickness improves film densification with the addition of layer deposition [13,21]. Thus, it can be concluded that the variation of the refractive index with the variation of film thickness is attributed to the increase in the film density for thicker films.…”
Section: Msementioning
confidence: 98%